Use of Olive Oil as an Effort to Prevent Damage to Skin Integrity: A Case Study - Nuryanah Nuryanah (Universitas Pendidikan Indonesia, 2023)
Background: Diabetes mellitus, also known as diabetes, is a collection of symptoms in a person due to increased blood sugar (glucose) levels, so that the pancreas works harder to produce insulin to balance sugar levels in the blood. The 2018 Riskesdas stated that the prevalence of DM in Indonesia had increased from 6.9% in 2013 to 8.5% in 2018. One of the herbal treatments in the study was olive oil. Olive oil is one of the natural ingredients recommended to help the healing process of diabetic wounds. The benefits of olive oil are able to treat diabetic wounds. Purpose: This case study is to find out whether olive oil can help heal damaged skin integrity in elderly people with diabetes. The research design used is a descriptive case study. The research subject is Mrs. A who is an elderly 54 years old. Results: The results of a case study conducted for 7 days of olive oil administration showed that there was a change in reaction to damage to the integrity of the skin of elderly people with diabetes mellitus after being given olive oil. Conclusion: there is an effect of olive oil on damage to the integrity of the skin of the elderly. By applying olive oil to dry skin areas. Suggestion: Olive oil is a non-pharmacological natural therapy method that can moisturize the skin in patients with diabetes mellitus. Giving olive oil can also be developed in the treatment room to help treat wounds in the elderly with diabetes mellitus.